ADVANCES IN ANALYTICAL TECHNIQUES FOR TOMATO SEED OIL: GC-MS QUANTIFICATION AND SIMPLIFIED PUFA ANALYSIS - REVATHI H; REVATHI A GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of this study was to delineate the fatty-acid profile of tomato seed oil (TSO) and assess the analytical efficacy of a streamlined one-step extraction-methylation approach in comparison to the traditional Folch protocol utilizing gas chromatography-mass spectrometry (GC-MS). Methods: TSO was extracted, transformed into fatty-acid methyl esters, and analyzed by GC-MS. The method validation encompassed linearity, precision, recovery, limits of detection (LOD), limits of quantification (LOQ), and statistical comparison by paired t-test and Bland-Altman analysis. Results and Discussion: Linoleic acid (48.16%), palmitic acid (17.22%), and oleic acid (9.18%) were recognized as the predominant fatty acids. Calibration demonstrated exceptional linearity (R2≥0.9999), with precision (%relative standard deviation≤5%) and recovery (95–105%) validating accuracy. The LOD ranged from 0.012 to 0.018 mg/mL, while the LOQ spanned from 0.036 to 0.054 mg/mL, demonstrating elevated sensitivity. No notable discrepancies were seen between the approaches (p>0.05), and Bland-Altman plots indicated robust agreement. Conclusion: TSO is an oil abundant in polyunsaturated fatty acids, and the streamlined method provides a swift, precise, and sustainable alternative for regular fatty acid profiling.